Mental health and the COVID-19 pandemic: looking back and moving forward. (December 2020) - Gavin, B.; Lyne, J.; McNicholas, F.
Abstract: COVID-19 continues to exert unprecedented challenges for society and it is now well recognised that mental health is a key healthcare issue related to the pandemic. The current edition of the Irish Journal of Psychological Medicine focusses on the impact of COVID-19 on mental illness by combining historical review papers, current perspectives and original research. It is important that psychiatrists leading mental health services in Ireland continue to advocate for mental health supports for healthcare workers and their patients, while aiming to deliver services flexibly. As the pandemic evolves, it remains to be seen whether the necessary funding to deliver effective mental healthcare will be allocated to psychiatric services. Ongoing service evaluation and research is needed as the myriad impacts of the pandemic continue to evolve. In a time of severe budgetary constraints, ensuring optimum use of scare resources becomes an imperative.